Vatican's Diplomacy in Global Child Protection - Muhammad Fajhriyadi Hastira (Jurnal Transformasi Global, 2025)
This study aims to analyze the influence and dynamics of the Vatican's moral authority as religious institutionalism on the global agenda for child protection through the forum “World Leaders Summit on Children's Rights.” This issue is relevant given the high rates of violence against children globally and the need for collaboration among cross-national actors in global governance. A qualitative approach was used through case study methods to explore the Vatican's public diplomacy strategies, religious diplomacy, and utilization of international institutional mechanisms. Data were collected by analyzing official Vatican documents, international organization reports, media archives, and academic literature published between 2020 and 2025. Data analysis was conducted using source triangulation and theory to ensure validity. The findings indicate that the Vatican plays a practical and strategic role as a norm entrepreneur with its dual role as a sovereign state and religious authority by combining moral legitimacy, religious symbols, and diplomatic networks to shape norms and policies for child protection. The effectiveness of this role depends on moral credibility, the ability to build cross-cultural coalitions, and inclusive communication strategies. This study contributes theoretically to developing religion-based diplomacy studies and practically provides a model of universal value advocacy for policymakers and international organizations.